Pemberdayaan Siswa SMP Melalui Program Psikoedukasi "Grow Calm, Learn Better" dalam Meningkatkan Kesejahteraan Psikologis dan Kemampuan Coping Stres - Cucut Arifa Rahman; Ni’matuzahroh Ni’matuzahroh; Rr Siti Suminarti Fasikhah (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The "Grow Calm, Learn Better" psychoeducational program was implemented as an effort to improve students' well-being in coping with academic stress at SMP Muhammadiyah 06 Dau in Malang Regency. This initiative was prompted by the high level of academic pressure affecting students' emotional state, emotional regulation, and coping skills. The activity was conducted involving 25 junior high school students, using Likert-scale questionnaires, observations, and participant satisfaction evaluations as assessment instruments. The results indicated an improvement in students' understanding of academic stress, emotional regulation, and stress coping, with the average score increasing from 2.76 to 4.12. Additionally, students demonstrated more adaptive behavioral changes, such as the ability to recognize emotions, control emotional responses, and apply positive coping strategies. The program also achieved a high level of participant satisfaction. Thus, mindfulness-based psychoeducation and social-emotional learning are effective in enhancing students' psychological well-being.